Karakterisasi Struktur Bawah Permukaan Menggunakan Inversi Data Gravitasi di Cekungan Ombilin - Fitria; A. Haris; Rinaldo (Jurnal Penelitian Pendidikan IPA, 2025)
The Ombilin Basin in West Sumatra is one of the oldest intermontane basins in Indonesia that has significant geological potential, especially in relation to coal content and possible petroleum systems. This study uses a three-dimensional gravity inversion method to model the distribution of subsurface density from a depth of 0 to 6000 meters. The purpose of this study is to examine the subsurface geological modeling in the Ombilin Basin and to be a reference in exploration geophysical studies in other basins in Indonesia that have similar characteristics. Corrected regional gravity data are used as input in the inversion process to reconstruct the relative density model of rocks. The inversion results show a low-density zone (Δg between -0.1995 to -0.0099 gr/cc) in the central and southwest parts of the basin associated with sedimentary deposits such as sandstone, shale, and coal. At depths of more than 4000 meters, a high-density zone is identified that reflects the presence of basement rocks or possible magmatic intrusions. This density distribution strengthens the understanding of the basin geometry and potential hydrocarbon traps. This study shows that the gravity inversion method is an effective and economical approach for subsurface geological interpretation, especially in areas with limited exploration data.